Spontaneous pneumothorax as manifestation of Marfan syndrome. (5th December 2013) - Viveiro, Carolina; Rocha, Patricia; Carvalho, Cristiana; Zarcos, Maria Manuel
Abstract : The authors describe a 16-year-old boy, previously healthy, who was admitted to our hospital for left-sided spontaneous pneumothorax. On physical examination he presented with marfanoid habitus. Pneumothorax was managed conservatively with resolution. Four months later he had a recurrence of left-sided pneumothorax and 1 week after that he presented with contralateral pneumothorax. He underwent video-assisted thoracoscopic surgery twice for bullectomy and pleurodesis. No further recurrence was stated. Additional investigation showed a prolapsed cardiac mitral valve and Marfan syndrome was confirmed genetically.